Psychiatric morbidity: a multilevel approach to regional variations in the UK. Issue 3 (June 1995) - Duncan, C; Jones, K; Moon, G
Abstract : STUDY OBJECTIVE–To establish whether regional variations in psychiatric morbidity in Britain constitute a distinctive geography of mental health arising from factors that are context-specific at area level or whether these variations are an artifact generated by sampling fluctuations and differing population compositions in areas. DESIGN–Multilevel modelling techniques were applied to data from the 1984-85 health and lifestyle survey. The outcome was the prevalence of psychiatric morbidity as recorded by the application of the general health questionnaire in this survey. SETTING–The analysis was undertaken simultaneously at the individual level, electoral ward level, and regional level for England, Wales, and Scotland. PARTICIPANTS–A total of 6572 adults were selected from the electoral register. MAIN RESULTS–Regional variations were detected in crude aggregate general health questionnaire scores but these were found to be the result of sampling fluctuations and varying regional population compositions rather than higher level contextual effects. There was certainly no evidence of a clear north-south distinction in psychiatric morbidity as was suggested by earlier work. In addition, the local neighbourhood did not seem to have any importance beyond the type of people who lived there. A number of individual characteristics was shown to be associated with mental wellbeing but a large degree of individual variation remained unexplained. CONCLUSIONS–In terms of low level psychiatric disturbance it seems that the characteristics of individuals have greater importance than the characteristics of areas, although the latter may still operate as important mediating factors. Multilevel modelling represents a robust statistical method of examining area variations in health outcomes and further work needs to be conducted, particularly on more serious psychiatric conditions.